Thermal runaway suppression effect of water mist on 18650-cylinder lithium-ion batteries with different cathode materials. (July 2022) - Liu, Xiaozhao; Xu, Dengji; Meng, Xiaokai; Lu, Zhumao; Chen, Yanjun; Liu, Changcheng; Huang, Que
Abstract: Currently, the potential thermal runaway (TR) hazard of lithium-ion batteries (LIBs) has attracted widespread attention. Fortunately, water mist (WM) has proven to be an effective way to suppress TR in LIBs. This article mainly studies the TR characteristics and the WM suppression effects of three types of 18, 650 cylinders with lithium iron phosphate (LFP), lithium cobalt oxide (LCO) and ternary nickel manganese cobalt (NMC) as the cathode materials. Based on the self-built platform, the TR suppression effect of pure WM and what with 5% NaCl additive by mass on three types of 18, 650 cylinders at different state of charge (SOC) was explored. The results reveals that the WM containing NaCl additive possesses better inhibition effect of TR than pure WM; the WM has the best suppression effect on the LFP. However, WM cannot efficiently curb the TR of LCO and NMC at 100% SOC. Advancing the spraying time to the initial burst can effectively control TR of LCO and NMC at 66% and 33% SOC. The mechanism of WM to suppress TR is mainly reflected in cooling, diluting oxygen, affecting flames, and reacting with flue gas. In order to effectively inhibit the TR of LIBs, not only should a suitable TR inhibitor be selected, but also the timing of spraying should be considered. Only when both are the best choices, it is possible to control the TR hazard in the bud.